Cardiac manifestations in sickle cell disease varies with patient genotype. (20th April 2018) - Guedeney, Paul; Lionnet, François; Ceccaldi, Alexandre; Stankovic Stojanovic, Katia; Cohen, Ariel; Mattioni, Sarah; Montalescot, Gilles; Bachmeyer, Claude; Isnard, Richard; Haymann, Jean‐Philippe; Hammoudi, Nadjib
Summary: Cardiac involvement is well characterized in sickle cell anaemia (SCA) but cardiac features associated with Haemoglobin SC (HbSC) disease are mostly unknown. We compared 60 patients with HbSC disease (median age 31 years, 25 men) to 60 SCA patients and 60 controls matched for age and gender. Left ventricular ejection fraction (LVEF), left ventricle (LV) mass index (LVMi), cardiac index and peak tricuspid regurgitation velocity (TRV) were measured using echocardiography. LV filling pressures were assessed using the ratio of early diastolic transmitral velocity to tissue velocity (E/e' ratio). The LVMi was higher in both genotypes compared to controls. However, whereas LV hypertrophy was observed only in 3(5%) HbSC patients, this condition was diagnosed in 27(45%) SCA patients ( P < 0·0001). While cardiac index and TRV were similar in HbSC compared to controls, SCA patients exhibited elevated cardiac output and TRV. LVEF was similar in the 3 groups. However, both genotypes had a higher E/e' ratio compared to controls. Cardiac involvement in SCA was related to anaemia and haemolysis, while LV diastolic dysfunction and TRV in HbSC disease patients were related to arterial hypertension and overweight comorbidities. In summary, cardiac involvement and its determinants are different in HbSC disease and SCA. Patient's genotype should be considered with regard to the echocardiographic indications and findings.